Argentina’s naval programmes in World War II - Waldmann Júnior, Ludolf (2020)
Argentina had a troubled trajectory during World War II, assuming a controversial neutrality during a period of great political instability in her history. As several authors noted, a sensitive political issue in this period was the re-equipment of her armed forces, something that had repercussions both domestically and externally, however there is almost no discussion on the content of these proposals for the acquisition of military materiel. Considering the importance of this issue for political developments in Argentina, this paper seeks to understand the plans for naval modernization during the war, relating them to the context in which they were presented. Thus, we emphasize the importance of the external political scenario in discussions about naval programmes, especially in view of the relative decline in Argentine power at the regional level. Internally, the role of civil-military relations must be observed. Finally, we pointed out that the fleet renewal plans initially reflected the pre-war naval policy, focusing on the regional scope and ensuring Argentine superiority, but its content was modified as new naval technologies and political developments changed the scenario.